Effectiveness of Ascorbic Acid and Calcium Chloride on Physicochemical Properties of Fresh Cut Jackfruit Bulb - Zaidi, Nur Amirah Filzah (Enhanced Knowledge in Sciences and Technology, 2022)
Jackfruit with the scientific name, Artocarpus heterophyllus L. was believed to have originates in rainforests of India. It is known as one of the most nutritious fruits. In this study, the jackfruit was deseeded and cut into the desired size which is 2 cm x 2 cm. The untreated sample or also known as control sample was left for storage after sanitized with chlorinated water (30 ppm) for 5 minutes. The other sample was treated with 1% of calcium chloride and 0.25% of ascorbic acid. All of the samples were stored in zip lock bag according to day of analysis and was left in a chilled condition for 17 days. A total of 7 analysis was done which are pH, total soluble solid, titratable acidity, ascorbic acid content, color, texture and moisture content. The sample was analyzed for day 0, 3, 6, 10, 13, 17 and was done in triplicate for each analysis. The texture of the fresh cut jackfruit bulb dipped with calcium chloride was firmer than ascorbic acid dipped samples. Both chemicals were proven to be effective on the physicochemical properties of the fresh cut jackfruit, as it shows a decrease trend in analysis of pH, corresponding to increase of titratable acidity. The analysis of total soluble solid and ascorbic acid content decreases by time. Analysis of color which is the value of a* that indicates redness was the highest in ascorbic acid dipped samples. The calcium chloride helps maintained the value of L* that indicates lightness and b* due to its role to inhibit the color changes of the sample. To conclude, calcium chloride and ascorbic acid able to maintain the physicochemical properties of fresh cut jackfruit bulb while act as firming and anti-browning agent throughout the 17 days of storage.